A computational study of hydrogen embrittlement phenomena in an iron nickel based alloy - Simonetti, Sandra Isabel (2009)
The interaction between H atoms and a Fe50Ni50 alloy containing vacancies was studied. The energy of the system was calculated by the atom superposition and electron delocalization molecular orbital (ASED-MO) method. The electronic structure was studied using the concept of density of states (DOS) and crystal orbital overlap population (COOP) curves. The minimum energy position for the H atom in the vacancy region was found at 1.32 Å from the vacancy centre. The changes in the electronic structure of Fe and Ni atoms near the vacancies were analyzed. The interactions mainly involve Fe and Ni metal 4s and 4p atomic orbitals, the most important being the contribution of Fe orbitals. Fe–Fe, Fe–Ni and Ni–Ni bonds weakened as new Fe–H ones were formed. The effect of H atoms is limited to its first neighbours. The detrimental effect of H atoms on the metallic bonds can be related to the mechanism for H embrittlement.